A ISIJWILI SE AFRIKA: Alkebulan - sisonke, limise (Open Mic: A Creative Writing Journal, 2024)
The poem is about the current state of Afrika the suffering of our continent and the possible reasons that have lead us to where we are. This poem give a insight of our spritual importants of African people and iving and connecting to our roots.